Pengaruh Good Corporate Governance terhadap Innovation Performance - Muhammad Pondrinal; Rozi Destian; Hanna Pratiwi; Desi Ilona (Universitas Medan Area, 2022)
his study aims to investigate the implementation on Good of Corporate Governance in enhancing innovation performance for 217 companies listed on IDX from 2014-2018. The researchers interested to study this topic because of there is no prior study investigate about Good Corporate Governance and innovation performance as dependent variable. Good Corporate governance in this study is performed by gender of the board of directors, the skills of the board of directors, and the size of the board of directors. Company size and profitability are as variables control. This research used panel data analysis with fixed effect models. The results of this study indicate that the gender of the board of directors, the size of the board of directors, and profitability have no significant impact on innovation performance. While the skills of the board of directors have a negative and significant effect on innovation performance. Company size has a positive and significant effect on innovation performance. Implementation of Good Corporate Governance does not improve innovation performance in Indonesia’s company.